Faktor yang berkaitan dengan Status Imunisasi Campak-Rubella Lanjutan pada Anak Usia 20-59 Bulan di Desa Labuha Kecamatan Bacan - Raihan Alfisahrin Safran; Elpira Asmin; Rizki Ayu (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2025)
Measles is an infectious disease caused by a viral infection. The measles virus is known as Morbilivirus. Measles is a disease that causes a systemic rash and there are several clinical manifestations that can cause complications. The purpose of this study was to determine factors related to advanced measles-rubella immunization status in children aged 20-59 months in Labuha Village, Bacan District in 2023. This study was an observational analytic study with a cross-sectional approach using primary data obtained from 143 respondent. The sampling technique used is Simple Random Sampling. The results of this study showed that out of 143 children aged 20-59 months in Labuha Village who had received advanced measles-rubella immunization, 67 children (46.9%), while children who did not receive advanced measles-rubella immunization, were 76 children (53, 1%). The results showed that the related factors were education (p=0.004), knowledge (p=0.002), basic immunization status (p=0.034). The variable that has no relationship is the mother's employment status (p=0.102). The conclusion of this study is that there is a relationship between education level, level of knowledge, and children's basic immunization status. However, there was no relationship between the mother's employment status and the measles-rubella immunization status. It is hoped that the Labuha health center will improve education and outreach regarding immunization so that it can motivate people to take part in routine immunization programs.